Physical and chemical indicators of raw spent grain - A. S. Danilchenko; K. R. Siyukhov; T. G. Korotkova; V. N. Khachaturov (Новые технологии, 2021)
The results of experimental studies of physical and chemical indicators and amino acid composition of raw brewer’s grains from Belorechensky (the Krasnodar Territory) and Maykop (the Republic of Adygea) br eweries have been presented. The purpose of the research is to compare the physicochemical parameters and amino acid composition of raw brewer’s grains obtained pneumatically at the Belorechensk brewery and hydraulically at the Maykop brewery. Analyzes carried out in an accredited laboratory and testing center have shown that fresh grains from both breweries are non-toxic. Both breweries use PILSNER MALT by «Kurskiy Malt» and produce beer using classic technology. The content of sugar and starch in absolutely dry matter is higher in brewer’s grains of the Maykop brewery, which indicates a deeper additional sugar starch used in the technology of the Belorechensk brewery. The presence of essential amino acids methionine, arginine, valine, threonine, etc. characterizes the nutritional value of the grain. The content of crude protein in the brewer grains of the Belorechensk brewery is higher compared to that in the Maykop brewery grains, 5,1% and 4,2%, respectively, and the content of nitrogen-free extractive substances is higher in the brewer grains of the Maykop brewery and makes up 9,3% and 8,8% in spent grains of the Belorechensk brewery. The data obtained are consistent with the data of other researchers. Due to the high moisture content in the Maykop brewer’s grains, its indicators have been determined after moisture draining through a sieve. Analysis of the technological stages of beer production has shown that a pasteurization unit was installed at the Belorechensk brewery before bottling beer, which helps to increase its shelf life and destroy the active action of microorganisms, but to reduce the saturation of the beer taste.